2020
DOI: 10.3354/aei00343
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in the rockpool shrimp Palaemon elegans following long-term exposure to low doses of the anti-parasitic drug teflubenzuron

Abstract: Anti-parasitic drugs used to control sea lice infestations in the salmonid aquaculture industry are a growing environmental concern due to their potential impacts on non-target crustacean species. This study examined the lethal effects of teflubenzuron, a common in-feed pharmaceutical drug used on Norwegian salmon farms, on a non-target species, rockpool shrimp Palaemon elegans, following an extended exposure period. The standard daily dose for treating salmon is 10 µg teflubenzuron g −1 fish. Adult shrimp wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…However, single types of contaminants adversely affected survival when applied at ten times the ambient concentrations. This is line with previous studies conducted on the pink shrimp Pandalus montagui, where researchers a reported a 10% increase in the mortality levels with higher pollutant dosage [75]. Note, however, the reduced survival of shrimp when mercury was one of the pollutants involved in the combination of contaminants.…”
Section: Discussionsupporting
confidence: 92%
“…However, single types of contaminants adversely affected survival when applied at ten times the ambient concentrations. This is line with previous studies conducted on the pink shrimp Pandalus montagui, where researchers a reported a 10% increase in the mortality levels with higher pollutant dosage [75]. Note, however, the reduced survival of shrimp when mercury was one of the pollutants involved in the combination of contaminants.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown that benzoylphenylurea insecticides are highly toxic to crustaceans that undergo moulting, including shrimp, and lobsters (Samuelsen et al, 2014;Bechmann et al, 2018;Samuelsen et al, 2020). There is, however, limited information currently available on the levels of these compounds present in the marine environment around Norwegian fish farms consequently, it is difficult to assess whether diflubenzuron and teflubenzuron pose a risk to marine biota in the wild as well as to human health.…”
Section: Introductionmentioning
confidence: 99%